Educação física escolar e inclusão de alunos com deficiência: um estudo em escolas do ensino regular da Rede Pública Estadual de São Paulo - Sousa, Angela Tavares de (2009)
The present study, accomplished during 2008, aimed at the analysis of the scholar inclusion of handicapped students at physical education classes from regular teaching at Sao Paulo public state network. This way, we try to identify the position of the physical education teachers towards the effective conditions offered to them by superior sectors (scholar organization, specialized support, specific pedagogical and material resources, architectural and curricular adaptations), as means to develop a work that guarantee the scholar inclusion of handicapped students at regular teaching. The hypothesis that led this investigation were the following: the public authorities do not guarantee the resources commended by CNE/CEB Resolution n. 02/2001, establishing the national guidance for special education at basic education; the differences that occur on the effective conditions at the researched schools, despite being so close and serving the same community; and that there is a low critical attitude of the researched teachers derived from a teacher habitus built from a precariousness principle that generally characterizes the formation and performance of teachers at fundamental teaching in Brazil. So, three schools from this network in Itaquaquecetuba just separated by walls but showing completely different conditions towards pedagogical and physical infra-structure were investigated. As methodological procedures we used half-structured interviews with the physical education teachers from these schools and some registers (documents, photographs and visual descriptions) trying to compare what the legal rules determine and what is really offered to these teachers (physical adaptations, didactic material and pedagogical support). Pierre Bourdieu s contributions were used as theoretical basis, especially the habitus concepts, as well as the processes of exclusion occurred inside the school. The perspective adopted by Bueno has contributed to the discussion and analysis about deficiency and scholar process. The main points show us that despite the existence of a federal guiding document that rules a group of operational determinations that focus the high quality scholar inclusion for handicapped students, they are not really offered and, even more, the teachers, adapted to the habitus of the precarious conditions that characterize the teachers formation and actions, in spite of noticing the lack of resources, do not assume a critical position face to the precariousness, treating it as inherent to the teaching function. The differences among the institutions were not enough to the school with best conditions be able to have a more qualified inclusion of the students because the ethos of precariousness is also assumed by the educators, whereas despite the teachers are aware that it had best infra-structure conditions towards availability of resources for scholar inclusion it had the same bad points of the others, making this less evident precariousness naturalized